Transgenic Hydra allow in vivo tracking of individual stem cells during morphogenesis - Wittlieb, Jörg; Lohmann, Jan U. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
Understanding the evolution of development in large part relies on the study of phylogenetically old organisms. Cnidarians, such as Hydra, have become attractive model organisms for these studies. However, despite long-term efforts, stably transgenic animals could not be generated, severely limiting the functional analysis of genes. Here we report the efficient generation of transgenic Hydra lines by embryo microinjection. One of these transgenic lines expressing EGFP revealed remarkably high motility of individual endodermal epithelial cells during morphogenesis. We expect that transgenic Hydra will become important tools to dissect the molecular mechanisms of development at the base of the Metazoan tree.
Gesehen am 09.05.2017